Severe and fatal adverse events of immune checkpoint inhibitor combination therapy in patients with metastatic renal cell carcinoma: a systematic review and meta-analysis - Feng, Yao-Ning; Xie, Guang-Yu; Xiao, Li; Mo, Dun-Chang; Huang, Jian-Feng; Luo, Peng-Hui; Liang, Xiu-Juan (Frontiers in Immunology, 2023)
Introduction：Immune checkpoint inhibitor (ICI)-combination therapy has changed the treatment landscape in metastatic renal cell carcinoma (mRCC). However, little evidence exists on the treatment-related severe adverse events (SAEs) and fatal adverse events (FAEs) of ICI-combination therapy in mRCC. Method：We included randomized controlled trials (RCTs) of ICI-combination therapy versus conventional tyrosine kinase inhibitor (TKI) targeted therapy in mRCC. Data on SAEs and FAEs were analyzed. Results：Eight RCTs (n = 5380) were identified. The analysis showed that no differences in SAEs (60.5% vs 64.5%) and FAEs (1.2% vs 0.8%) were found between ICI and TKI groups (odds ratio [OR], 0.83, 95%CI 0.58−1.19, p = 0.30 and OR, 1.54, 95%CI 0.89−2.69, p = 0.12, respectively). ICI-combination therapy was associated with lower risk of hematotoxicities, including anemia (OR, 0.24, 95%CI 0.15-0.38, p < 0.00001), neutropenia (OR, 0.07, 95%CI 0.03-0.14, p < 0.00001), and thrombocytopenia (OR, 0.05, 95%CI 0.02−0.12, p < 0.00001), but with increased risks of hepatotoxicities (ALT increase [OR, 3.39, 95%CI 2.39-4.81, p < 0.00001] and AST increase [OR, 2.71, 95%CI 1.81−4.07, p < 0.00001]), gastrointestinal toxicities (amylase level increase [OR, 2.32, 95%CI 1.33-4.05, p = 0.003] and decreased appetite [OR, 1.77, 95%CI 1.08-2.92, p = 0.02]), endocrine toxicity (adrenal insufficiency [OR, 11.27, 95%CI 1.55-81.87, p = 0.02]) and nephrotoxicity of proteinuria (OR, 2.21, 95%CI 1.06−4.61, p = 0.03). Conclusions：ICI-combination therapy has less hematotoxicity but more specific hepatotoxicity, gastrointestinal toxicity, endocrine toxicity, and nephrotoxicity than TKI in mRCC, with a similar severe toxicity profile in general.